Fabrication and characterization of polycaprolactone/calcium sulfate whisker composites (eXPRESS Polymer Letters, 2011)
Polycaprolactone (PCL)/calcium sulfate (CS) whisker composites have been fabricated by melt blending and coprecipitation methods respectively. Scanning electron microscope (SEM) was used to observe the microstructure of the composites. The crystallization and thermal properties were characterized by polarized optical microscope (POM), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). For composites prepared by melt blending method, experiment results show that average length of the whiskers is shortened. The crystallization perfection of PCL in composites is improved by adding whiskers. The flexural strength increases whereas the impact strength decreases. For composites prepared by coprecipitation method, whisker addition worsens the crystallization perfection of PCL. An improvement of 21% in flexural strength and 22% in impact strength has been achieved for the composite with 15 wt% of whiskers.